GAMEPLANS: a template for robust digital evidence strategy development - Horsman, Graeme (Wiley, 2025)
Law enforcement officers should now expect to encounter forms of digital evidence at most of their inquiries, and as a result ensure they are prepared to effectively deal with it. This should involve the production of a digital evidence strategy (DES) which describes those actions required of any investigative team to effectively identify, collect, examine, and evaluate any digital devices/data, while also defining the circumstances for when it is appropriate to conduct such tasks. To help officers to produce robust DESs this work provides a DES template which utilizes the “GAMEPLANS” acrostic to identify nine fundamental components that are required of all DESs—“G”–Grounds for investigation; “A”–Authorization; “M”–Method of investigation; “E”–Evaluation of the meaning of any findings; “P”–Proportionality; “L”–Logic; “A”–Agreement; “N”–Necessity; “S”–Scrutiny. Each of these components are described including the sub‐tasks that are contained within each, which any officer constructing a robust and effective DES must address (and provide evidence of having addressed). To support this, a DES template file is also provided, which can be utilized by officers.
Keywords: digital evidence; digital evidence strategy; digital forensics; digital investigation; police; 4402 Criminology; 44 Human Society; Legal & Forensic Medicine; 3199 Other biological sciences; 3499 Other chemical sciences